2020
DOI: 10.3390/ani10081417
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of microRNAs during Embryonic Skeletal Muscle Development in the Shan Ma Duck

Abstract: Poultry skeletal muscle provides high quality protein for humans. Study of the genetic mechanisms during duck skeletal muscle development contribute to future duck breeding and meat production. In the current study, three breast muscle samples from Shan Ma ducks at embryonic day 13 (E13) and E19 were collected, respectively. We detected microRNA (miRNA) expression using high throughput sequencing following bioinformatic analysis. qRT-PCR validated the reliability of sequencing results. We also identified targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Then, fifteen small libraries (five from each stage) were used for the Illumina/Solexa deep sequencing. Ligation of the total short RNAs (~18–26 nt in length), the reverse transcription, and PCR were performed according to previous work [ 21 ]. Finally, the amplification products were used directly for cluster generation and submitted to LC-Bio (Hangzhou, China) for the single-end sequencing on an Illumina Hiseq2500.…”
Section: Methodsmentioning
confidence: 99%
“…Then, fifteen small libraries (five from each stage) were used for the Illumina/Solexa deep sequencing. Ligation of the total short RNAs (~18–26 nt in length), the reverse transcription, and PCR were performed according to previous work [ 21 ]. Finally, the amplification products were used directly for cluster generation and submitted to LC-Bio (Hangzhou, China) for the single-end sequencing on an Illumina Hiseq2500.…”
Section: Methodsmentioning
confidence: 99%
“…Then, ten small libraries (four samples from the NC group and six samples from the HC group) were used for Illumina/Solexa deep sequencing. Ligation of the total short RNAs (~18–26 nt in length), reverse transcription and PCR were performed according to previous work [ 20 ]. Finally, the amplification products were used directly for cluster generation and were then submitted to LC-Bio (Hangzhou, China) for single-end sequencing on an Illumina Hiseq2500.…”
Section: Methodsmentioning
confidence: 99%
“…Muscle-specific microRNAs, called MyomiRs, are expressed in the muscle cells, although they are also expressed in several other tissues (McCarthy, 2008). Li et al found detected 279 novel miRNAs in the breast muscle of ducks, indicating the importance of miRNAs in muscle development and maturation (Li et al, 2020). Among these, miRNA-1 and miRNA-133 have been suggested to be crucial factors for duck skeletal muscle proliferation and differentiation.…”
Section: Duck Meatmentioning
confidence: 99%
“…Li et al. found detected 279 novel miRNAs in the breast muscle of ducks, indicating the importance of miRNAs in muscle development and maturation ( Li et al, 2020 ). Among these, miRNA-1 and miRNA-133 have been suggested to be crucial factors for duck skeletal muscle proliferation and differentiation.…”
Section: Introductionmentioning
confidence: 99%